2012
DOI: 10.1634/theoncologist.2011-0466
|View full text |Cite
|
Sign up to set email alerts
|

A Second-Generation MicroRNA-Based Assay for Diagnosing Tumor Tissue Origin

Abstract: Background. Cancers of unknown primary origin (CUP) constitute 3%-5% (50,000 to 70,000 cases) of all newly diagnosed cancers per year in the United States. Including cancers of uncertain primary origin, the total number increases to 12%-15% (180,000 to 220,000 cases) of all newly diagnosed cancers per year in the United States. Cancers of unknown/uncertain primary origins present major diagnostic and clinical challenges because the tumor tissue of origin is crucial for selecting optimal treatment. MicroRNAs ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
97
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(101 citation statements)
references
References 31 publications
(4 reference statements)
4
97
0
Order By: Relevance
“…This research group recently developed a second-generation microarray assessing the levels of 64 miRNAs to identify 42 tumor types. 25 The assay was validated on a set of 509 blinded samples and showed a sensitivity of 85%.…”
Section: Occ-1mentioning
confidence: 99%
“…This research group recently developed a second-generation microarray assessing the levels of 64 miRNAs to identify 42 tumor types. 25 The assay was validated on a set of 509 blinded samples and showed a sensitivity of 85%.…”
Section: Occ-1mentioning
confidence: 99%
“…Gene expression profiling assays correctly identified the site of origin in 85% of cases in blinded studies of tumors of known origin, and was found to favorably compare with IHC staining (17,18). The best use of gene expression profiling to form a diagnosis appears to be for cases with inconclusive IHC staining.…”
Section: Discussionmentioning
confidence: 92%
“…The CancerTYPE ID assay is a 92-gene reverse transcription-polymerase chain reaction assay that allows the identification of 30 main tumor types and 54 subtypes (17). There is also another gene expression profiling assay currently commercially available, which uses 64 tissue-specific microRNAs to enable the identification of 42 tumor types, using a microarray technology known as the Cancer Origin Test (Rosetta Genomics, Rehovot, Israel) (18). These two assays were validated using biopsies of tumors from known primary sites.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, some diagnostic tests employing ncRNA are already commercially available 13,[95][96][97] , with many others expected to follow.…”
Section: Five-year Viewmentioning
confidence: 99%